Succesful Treatment of Intermittant Hydrartrosis with Colchicine: A Case Report - Mehmet Adam,; Zafer Yıldız,; Gül Mete,; Berrin Leblebici, (Archives of Rheumatology, 2009)
Intermittent hydrarthrosis (IH) is a monoarticular disease of unknown etiology, characterized by episodic effusions, and it usually affects middle-aged women. Acute phase reactants are within normal range during attacks. Although this non-destructive disease has no definite treatment, non-steroidal anti-inflammatory drugs, intraarticular steroids, and radioactive and surgical synovectomy have been used. Here, we report a 37-year-old female with IH in whom successful remission was obtained with colchicine treatment. This case is of interest since to our knowledge there have been only two patients reported in the literature with remission of IH achieved by colchicine. (Turk J Rheumatol 2009; 24: 58-9)